Analysing the Factors Affecting Runs Scored by Batsmen in the ICC T20 World Cup 2016 - Siddhartho Das (International Journal of Advanced Science and Technology, 2020)
The ICC T20 World Cup[3] is an international tournament organised by the International Cricket Council. It is played among 16 teams. The top 10 teams are selected based on their ICC International T20 rankings up until a given deadline. The remaining teams are determined by a qualifying tournament, which is held just prior to the tournament. It comprises of associate nations. Most of these 6 teams have  not  been  given Test match status.Up until now, the tournament has been held every two years. However, the next edition will take place in 2020. It will  be  hosted by Australia. For the first time, it will be held after a      gap of four years. The tournament has been played 6 times so  far. Only the West Indies, the current champions, has won the tournament multiple times. The first ever T20 World Cup took place in South Africa in 2007. It was won by India, who emerged victorious in a closely contested final against their arch rivals, Pakistan. This set the tone for further editions of this tournament and international T20 cricket in general. England were the hosts of the 2009 edition and it was won by Pakistan. The third edition took place in 2010 and was won by England. The fourth edition, held in 2012, was won by The West Indies. The fifth edition, held in 2014, was won by Sri Lanka.This paper analyses the key factors affecting the batting performance of the top batsmen in the top 8 teams. Variables such as age, ODI average, T20 average, strike rates in both formats, number of fours and sixes were used to develop a non-linear regression model. The proposed model aims to provide insights on the factors which should be taken into account while the team management select their batsmen in the upcoming ICC World T20 in 2020.